2017
DOI: 10.1520/mpc20160083
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermochemically Surface-Hardened Titanium by Light Optical Microscopy

Abstract: Thermochemically treated titanium grade 2 and 5 were investigated by light optical microscopy and hardness indentation. Gaseous oxidation in oxygen and N2O containing atmospheres resulted in a diffusion zone of oxygen in solid solution in titanium with a hardness up to 1000HV. A surface scale consisting of oxide can be present depending on the treatment conditions. A new type of carbo-oxidation treatment was applied, where carbon and oxygen are simultaneously incorporated into the surface. This resulted in new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…An applied pressure of 3 Pa yielded the highest surface hardness of 1670 HV corresponding to a compound composition of TiC0.63O0.37, as determined by X-ray diffraction (XRD). [7] Gammeltoft-Hansen et al [8] successfully carbo-oxidised both commercially pure titanium (Grade 2) and Ti-6Al-4V in a gaseous atmosphere containing only carbon and oxygen, confirming the formation of TiCxO1-x by XRD. The obtained hardness was approximately 2200 HV for the compound phase and 1500 HV in the diffusion zone for Ti grade 2.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…An applied pressure of 3 Pa yielded the highest surface hardness of 1670 HV corresponding to a compound composition of TiC0.63O0.37, as determined by X-ray diffraction (XRD). [7] Gammeltoft-Hansen et al [8] successfully carbo-oxidised both commercially pure titanium (Grade 2) and Ti-6Al-4V in a gaseous atmosphere containing only carbon and oxygen, confirming the formation of TiCxO1-x by XRD. The obtained hardness was approximately 2200 HV for the compound phase and 1500 HV in the diffusion zone for Ti grade 2.…”
Section: Introductionmentioning
confidence: 93%
“…The obtained hardness was approximately 2200 HV for the compound phase and 1500 HV in the diffusion zone for Ti grade 2. [8] Very recently, it has also been shown that three interstitial elements (nitrogen, carbon and oxygen) can be incorporated into the surface of titanium grade 2, resulting in a high total interstitial solid solubility. [9] A few examples of surface engineering of Ti-based AM components have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, complex-shaped metal components are much cheaper than their equivalent ceramic ones. In this applicative domain, titanium alloys are by far the most interesting choice and can give rise to a tremendous amount of research (see, for example, [ 3 , 8 , 25 , 26 , 39 , 42 , 43 , 50 , 62 ]).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Nitriding can be achieved with a variety of techniques [ 3 ], the most popular ones being namely plasma, implantation, and gas or a combination of them (PBII) [ 4 ]. Nitriding methods have been applied to a number of different metals and alloys [ 5 , 6 , 7 , 8 , 9 , 10 ]. Below, we illustrate the mechanical strengthening achieved with steel and titanium alloys that have been the most successful.…”
Section: Introductionmentioning
confidence: 99%
“…This can be alleviated by surface hardening of Ti by incorporation of interstitial elements, C, N and/or O, in the h.c.p. α crystal structure and via formation of interstitial compounds ( [1], [2], [3]). The solubility of carbon in α is maximally 0.08 wt% at 800 °C [4], higher contents entail formation of NaCl type δ carbide.…”
Section: Introductionmentioning
confidence: 99%